Rancang Bangun Aplikasi Pengendalian Stok Produk Pada Zilch Streetwear Surabaya - Triwibowo, Aris; jusak, Jusak; churniawan, Agus dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Stock control products are important at Zilch Streetwear Surabaya because keeping the inventory levels of stock products at optimal levels so as to obtain savings, but in the implementation, Zilch Streetwear having problems, demand for the amount of product that is uncertain in each period make Zilch Streetwear trouble estimated demand for the product in the future. Inaccuracy in determining the timing and amount of products will be ordered lead out of stock and delay the fulfillment of product orders to retailers and customers. Based on the existing problems above, Zilch Streetwear need an application that is able to determine how the number of product items will be ordered in a period and when reordering the product. Stages of making this application begins with communication, planning, modeling, construction, and operation. After been tested, the application, can generate sales data, purchasing data, stock data products, the data inventory planning, inventory planning reports, stock reports, purchasing reports, and sales reports. This application also able to provide information order quanitity and reorder points better than the previous operational inventory planning